Feeding disorders of childhood - Almenara-Vargas, Carlos (2005)
The feeding disorders in the childhood have a relative short history in the psychiatry. This communication is a review of these disorders according the classification proposed by the group work directed by Irene Chatoor. Some remarks about the importance of these disorders for the psychoanalysis and a brief description of two clinical vignettes are included in this paper.